Reduction of Pyrrolizidine Alkaloid Levels in Comfrey (Symphytum officinale) Hairy Roots by RNAi Silencing of Homospermidine Synthase - Kruse, Lars H.; Stegemann, Thomas; Jensen-Kroll, Julia; Engelhardt, Annika; Wesseling, Anne-Maria; Lippert, Annemarie; Ludwig-Müller, Jutta; Ober, Dietrich (Planta Medica, 2019)
Comfrey is a medicinal plant, extracts of which are traditionally used for the treatment of painful inflammatory muscle and joint problems, because the plant contains allantoin and rosmarinic acid. However, its medicinal use is limited because of its toxic pyrrolizidine alkaloid (PA) content. PAs encompass more than 400 different compounds that have been identified from various plant lineages. To date, only the first pathway-specific enzyme, homospermidine synthase (HSS), has been characterized. HSS catalyzes the formation of homospermidine, which is exclusively incorporated into PAs. HSS has been recruited several times independently in various plant lineages during evolution by duplication of the gene encoding deoxyhypusine synthase (DHS), an enzyme of primary metabolism. Here, we describe the establishment of RNAi knockdown hairy root mutants of HSS in Symphytum officinale. A knockdown of HSS by 60 – 80% resulted in a significant reduction of homospermidine by ~ 86% and of the major PA components 7-acetylintermedine N-oxide and 3-acetylmyoscorpine N-oxide by approximately 60%. The correlation of reduced transcript levels of HSS with reduced levels of homospermidine and PAs provides in planta support for HSS being the central enzyme in PA biosynthesis. Furthermore, the generation of PA-depleted hairy roots might be a cost-efficient way for reducing toxic by-products that limit the medicinal applicability of S. officinale extracts.
Keywords: Symphytum officinale; alkaloid extraction; transgenic tissue culture; transcript quantification; Boraginaceae